Evidence on single-molecule transport in electrostatically-gated molecular transistors - Bâldea, Ioan; Köppel, Horst (Physics letters, 2012)
We show that, if adequately formulated for molecular electronics, the barrier picture can quantitatively reproduce the currents and describe the orbital gating in the molecular transistors fabricated by Song et al. [H. Song, Y. Kim, Y.H. Jang, H. Jeong, M.A. Reed, T. Lee, Nature 462 (2009) 1039]. Based on our results, we demonstrate (i) that the measured current represents the contribution of a single molecule, and (ii) the linear dependence of the molecular orbital energy offset εg on the voltage Vt at the Fowler-Nordheim minimum, validating thereby the transition voltage spectroscopy for the gated single molecule devices of Song et al.